Pengaruh Gaya Kepemimpinan Demokratis Kepala Sekolah Terhadap Kinerja Guru di SMK Negeri 2 Siatas Barita - Medi Wagi Berutu; Lasmaria Lumban Tobing; Rogate A.T Gultom (International Forum of Researchers and Lecturers, 2024)
The aim of this research is to determine the influence of the principal's leadership style on teacher performance at SMK Negeri 2 Siatas Barita in 2023. The method used in this research is a quantitative method with inferential statistics. The population is all 64 teachers at SMP Negeri 4 Pollung and this research is a population study. Data was collected using a positive closed questionnaire with 40 items. The results of data analysis show that there is a positive and significant influence of the principal's democratic leadership style on teacher performance at SMK Negeri 2 Siatas Barita in 2023: 1) Test the analysis requirements: a) test the positive influence, the value of rxy = 0.594 > rtable(=0) .05,n=64) = 0.244, thus it is known that there is a positive influence between variable )= 2,000, thus there is a significant relationship between variable X and variable Y. 2) Effect test: uyu88. a) Test the regression equation, obtained the regression equation Y ̂=